Nucleotide sequence and evolution of the 18S ribosomal RNA gene in maize mitochondria. - Chao, S (1984)
The nucleotide sequence of the gene coding for the 18S ribosomal RNA of maize mitochondria has been determined and a model for the secondary structure is proposed. Dot matrix analysis has been used to compare the extent and distribution of sequence similarities of the entire maize mitochondrial 18S rRNA sequence with that of 15 other small subunit rRNA sequences. The mitochondrial gene shows great similarity to the eubacterial sequences and to the maize chloroplast, and less similarity to mitochondrial rRNA genes in animals and fungi. We propose that this similarity is due to a slow rate of nucleotide divergence in plant mtDNA compared to the mtDNA of animals. Sequence comparisons indicate that the evolution of the maize mitochondrial 18S, chloroplast 16S and nuclear 17S ribosomal genes have been essentially independent, in spite of evidence for DNA transfer between organelles and the nucleus.